Studying the effects of McRoberts and neonate-focused maneuvers on the neonatal brachial plexus during shoulder dystocia - Iaconianni, Joy A.; Bakhri, Rania; Gonik, Bernard; Balasubramanian, Sriram; Singh, Anita (Frontiers in Bioengineering and Biotechnology, 2025)
This study investigates the effects of clinical delivery maneuvers on neonatal brachial plexus (BP) during complicated birthing scenarios such as shoulder dystocia. Shoulder dystocia occurs when the anterior shoulder of the neonate is obstructed behind the maternal symphysis pubis and prevents the delivery of the neonate. Maneuvers such as McRoberts, application of suprapubic pressure (SPP), oblique positioning, and posterior arm delivery are performed sequentially to alleviate the obstruction. This study used MADYMO, a computer software program, to simulate these maneuvers during shoulder dystocia while maternal endogenous forces (82N and 129N) were applied. The recorded outcomes were the magnitude of neonatal BP stretch during delivery and the amount of clinician-applied traction (CAT) force, if required, to achieve delivery. The lithotomy position was treated as the baseline and compared to the McRoberts position, at 82N and 129N maternal forces. Additionally, in McRoberts position, at 82N and 129N maternal forces, neonate-focused maneuvers were applied, and the clinician applied traction (CAT) force, if required, to achieve delivery was recorded along with the resulting neonatal BP stretch. The simulations, at 82N maternal force, reported a decrease in required CAT force in the McRoberts position compared to the lithotomy position. The results of the neonate-focused maneuvers reported a further decrease in the CAT force and the resulting BP stretch. Furthermore, increasing SPP from 40N to 100N reported no required CAT force for delivery along with decreased BP stretch. Oblique positioning further decreased the BP stretch, and the posterior arm delivery of the neonate resulted in the least amount of BP stretch. No CAT forces were required during these maneuvers. The simulations, at 129N maternal force, reported similar trends of reduced BP stretch during delivery except no CAT forces were required during any simulated conditions. Findings from this study help understand the effects of McRoberts position and neonate-focused maneuvers on neonatal brachial plexus during complicated shoulder dystocia delivery. The reported required delivery forces, both maternal and CAT also lay the groundwork for clinician training and education while guiding the development of preventative approaches that can limit neonatal injuries.